Identification and Biological Characterization of the Pyrazolo[3,4-d]pyrimidine Derivative SI388 Active as Src Inhibitor - Claudia Contadini; Claudia Cirotti; Anna Carbone; Mehrdad Norouzi; Annarita Cianciusi; Emmanuele Crespan; Cecilia Perini; Giovanni Maga; Daniela Barilà; Francesca Musumeci; Silvia Schenone (Pharmaceuticals, 2023)
Src is a non-receptor tyrosine kinase (TK) whose involvement in cancer, including glioblastoma (GBM), has been extensively demonstrated. In this context, we started from our in-house library of pyrazolo[3,4-d]pyrimidines that are active as Src and/or Bcr-Abl TK inhibitors and performed a lead optimization study to discover a new generation derivative that is suitable for Src kinase targeting. We synthesized a library of 19 compounds, 2a-s. Among these, compound 2a (SI388) was identified as the most potent Src inhibitor. Based on the cell-free results, we investigated the effect of SI388 in 2D and 3D GBM cellular models. Interestingly, SI388 significantly inhibits Src kinase, and therefore affects cell viability, tumorigenicity and enhances cancer cell sensitivity to ionizing radiation.